Smart Strategy to Boost Students’ Reading Comprehension - Syafi’i, Muhammad Lukman (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2015)
Reading as one of language skills plays significant roles in the teaching English as a foreign language. Since the teacher still uses the conventional way to teach reading, students‘ ability in reading comprehension seems still unsatisfactory yet. So, teacher should explore and develop new strategies. One of strategies in reading comprehension that can trigger our students to attain that purpose is SMART (Self Monitoring Approach for Reading and Thinking) strategy. This study is developing SMART strategy to boost the reading comprehension achievement of the ninth grade students. The research applies a collaborative classroom action research design in which the researcher and the collaborative teacher work together in preparing a suitable procedure of SMART strategy, designing the lesson plan, determining the criteria of success, implementing the action, observing, and doing reflection. The finding indicated that SMART strategy was successful to enhance students‘ motivation to be actively involved in the instructional process. The improvement on the students‘ participation was 75% in Cycle 1 and 87% in Cycle 2.